TINDAK TUTUR ILOKUSI DALAM NOVEL ARAH LANGKAH KARYA FIERSA BESARI - Mega Herlina; Laurensius Salem; Ahmad Rabi’ul Muzammil (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe thesis "The Act of Ilokusi in The Novel Arah Langkah by Fiersa Besari."This research is based on the basis that there is no misunderstanding of the reader'sspeech contained in the novel. The method used in this study is to use descriptivemethods. The form of research used is qualitative research. The data source in thisstudy is the novel Arah Langkah by Fiersa Besari. The data in this study is thefollow-up to the novel Arah Langkah by Fiersa Besari in the form of speech, words,.Data analysis tecniques use speaking techniques with context analysis.Based on theresults of data description and data analysis, it can be concluded that the action ofilokusi in the novel Arah Langkah by Fiersa Besari amounted to 125 speeches. First,the act of speech asertif ilokusi amounted to 31 speeches, second, the act of speechilokusi directive to 57 speeches, third, expressive ilokusi action amounted to 25speeches, fourth, the act of speech ilokusi komisif amounted to 6 speeches, fifth, theact of declarative ilokusi amounted to 6 speeches. The implementation of thisresearch relates to the study of Indonesian language in the curriculum of 2013 highschool (SMA) class XII.Keywords: Illocutionary Speech Acts, Novel Arah Langkah, Indonesian LanguageLearning